Developing Digital Learning Tools Based on 21st-century Skills for the Arabic Speaking Skill at Maulana Malik Ibrahim State Islamic University Malang - Asmaul Husna Maul; Inchinia Angger Rowin (UIN Syekh Wasil Kediri, Indonesia, 2025)
This research aims to develop digital educational media based on 21st-century skills for teaching speaking skills in Arabic in higher education. This study responds to the problems faced by students learning Arabic, particularly weak oral fluency, limited opportunities for communicative practice, and low motivation in learning. The research relied on the Research and Development (R&D) approach using the ADDIE model, which includes five main stages: Analysis, Design, Development, Implementation, and Evaluation. In the Analysis stage, students' needs were identified and educational problems were analyzed through observation and interviews. Then, digital educational media were designed, incorporating 21st-century skills during the Design stage, and developed into interactive materials in the Development stage. These media were reviewed by three experts: a content expert, an educational media expert, and a language expert. Subsequently, the field experiment was conducted on a sample of 50 students from the Arabic language education program using a pre-test and post-test design, with data collected through tests, questionnaires, and observation. The research results showed that the developed digital educational media has a high level of validity, with evaluation rates ranging between 88% and 92% among the three experts. The results of the pre-test and post-test also indicated a statistically significant improvement in Arabic speaking skills, as the average student scores increased from 65 in the pre-test to 85 in the post-test at a significance level of (p < 0.05). In addition, the results of the questionnaires and observations revealed an increase in students' motivation and active participation in speaking activities, such as dialogues, oral presentations, and group discussions, which indicates the effectiveness of digital educational media in improving speaking skills and developing learners' communication abilities. يهدف هذا البحث إلى تطوير وسائط تعليمية رقمية قائمة على مهارات القرن الحادي والعشرين لتعليم مهارة الكلام باللغة العربية في التعليم العالي. ويأتي هذا البحث استجابةً للمشكلات التي يواجهها طلبة تعليم اللغة العربية، ولا سيما ضعف الطلاقة الشفوية، وقلة فرص الممارسة التواصلية، وانخفاض الدافعية في التعلم. اعتمد البحث على منهج البحث والتطوير (Research and Development) باستخدام نموذج ADDIE الذي يتضمن خمس مراحل رئيسة، هي: التحليل، والتصميم، والتطوير، والتنفيذ، والتقييم. ففي مرحلة التحليل، تم تحديد احتياجات الطلبة وتحليل المشكلات التعليمية من خلال الملاحظة والمقابلة. ثم صُمِّمت الوسائط التعليمية الرقمية مع دمج مهارات القرن الحادي والعشرين في مرحلة التصميم، وطُوِّرت في صورة مواد تفاعلية في مرحلة التطوير. وقد خضعت هذه الوسائط للتحكيم من قبل ثلاثة خبراء، وهم: خبير المحتوى، وخبير الوسائط التعليمية، وخبير اللغة. وبعد ذلك، نُفِّذت التجربة الميدانية على عينة مكونة من (50) طالبًا وطالبة من برنامج دراسة تعليم اللغة العربية باستخدام تصميم الاختبار القبلي والبعدي، مع جمع البيانات من خلال الاختبارات، والاستبيانات، والملاحظة. ظهرت نتائج البحث أن الوسائط التعليمية الرقمية المطوَّرة تتمتع بدرجة عالية من الصلاحية، حيث تراوحت نسب التقييم بين 88٪ و92٪ لدى الخبراء الثلاثة. كما بينت نتائج الاختبار القبلي والبعدي وجود تحسن دال إحصائيًا في مهارة الكلام باللغة العربية، إذ ارتفع متوسط درجات الطلبة من 65 في الاختبار القبلي إلى 85 في الاختبار البعدي عند مستوى دلالة (p < 0.05). إضافة إلى ذلك، كشفت نتائج الاستبيانات والملاحظة عن ارتفاع مستوى دافعية الطلبة ومشاركتهم النشطة في أنشطة التحدث، مثل الحوار والعروض الشفوية والمناقشات الجماعية، مما يدل على فاعلية الوسائط التعليمية الرقمية في تحسين مهارة الكلام وتنمية مهارات التواصل لدى المتعلمين.